Sustained Downregulation of Vascular Smooth Muscle Acta2 After Transient Angiotensin II Infusion: A New Model of “Vascular Memory” - Pothen, Lucie; Verdoy, Roxane; De Mulder, Delphine; Esfahani, Hrag; Farah, Charlotte; Michel, Lauriane Y. M.; Dei Zotti, Flavia; Bearzatto, Bertrand; Ambroise, Jerome; Bouzin, Caroline; Dessy, Chantal; Balligand, Jean-Luc (Frontiers in Cardiovascular Medicine, 2022)
• Background: Activation of the renin-angiotensin-aldosterone system (RAAS) plays a critical role in the development of hypertension. Published evidence on a putative “memory effect” of AngII on vascular components is however scarce. Aim: to evaluate long-term effects of transient exposure to AngII on mouse heart and arterial tissue. Methods: blood pressure, cardiovascular tissue damage and remodeling, and systemic oxidative stress were evaluated in C57/B6/J mice at the end of a 2-week AngII infusion (AngII); 2 and 3 weeks after the interruption of a 2-week AngII treatment (AngII+2W and AngII +3W; so called “memory” conditions) and control littermate (CTRL). RNAseq profiling of aortic tissues was used to identify potential key regulated genes accounting for legacy effects on the vascular phenotype. RNAseq results were validated by RT qPCR and immunohistochemistry in a reproduction cohort of mice. Key findings were reproduced in a homotypic cell culture model. Results: 2 weeks AngII infusion induced cardiac hypertrophy and aortic damage, that persisted beyond AngII interruption and despite blood pressure normalization, with sustained vascular expression of ICAM1, infiltration by CD45+ cells, and cell proliferation associated with systemic oxidative stress. RNAseq profiling in aortic tissue identified robust Acta2 down regulation at transcript and protein levels (𝛼-Smooth Muscle Actin) that was maintained beyond interruption of AngII treatment. Among regulators of Acta2 expression, the transcription factor Myocardin (Myocd), exhibited a similar expression pattern. The sustained downregulation of Acta2 and Myocd was associated with an increase in H3K27me3 in nuclei of aortic sections from mice in the “memory” conditions. A sustained downregulation of ACTA2 and MYOCD was reproduced in cultured human aortic vascular smooth muscle cells upon transient exposure to Ang II. Conclusion: A transient exposure to Ang II produces prolonged vascular remodeling with robust ACTA2 downregulation, associated with an epigenetic imprinting supporting a “memory” effect despite stimulus withdrawal.